Cancer Stem Cells and Treatment of Cancer: An Update and Future Perspectives - Khan, Mudassir; Naeem, Mashal; Chaudary, Sana A.; Ahmed, Affan; Ahmed, Aftab (Current Stem Cell Research & Therapy, 2024)
Cancer stem cells (CSCs) play an essential role in tumour progression and metastasis. Stem cell ability of self-renewal enables it to persist over time, thereby contributing to cancer relapse or recurrence and also resistance to current therapies. Therefore, targeting CSCs emerged as a promising strategy of cancer treatment. CSCs exhibit differentiation, self-renewal, and plasticity, they contribute to formation of malignant tumours, also favors, metastasis, heterogeneity, multidrug resistance, and radiation resistance. Coventional cancer treatments predominantly target cancer cells that are not CSCs, CSCs frequently survive, eventually leading to relapse. This article focuses on the development of novel therapeutic strategies that combine conventional treatments and CSC inhibitors to eradicate cancer cells and CSCs, for the better and permanent treatment. However, the diversity of CSCs is a significant obstacle in the development of CSC-targeted therapies, necessitating extensive research for a better understanding and exploration of therapeutic approaches. Future development of CSC-targeted therapies will rely heavily on overcoming this obstacle.
Keywords: cancer remission